The sports media system in Arab media charters - A reading of the Emirati journalistic code of ethics - - Taj al-Sir Faqir Omar, Imad al-Din (sports creativity, 2025)
Sports media is a prominent and influential field of communication and media, with a significant presence and a vital aspect of life. It boasts its own audience, activities, tools, and both general and specialized media outlets. Throughout its long history, sports media has positively contributed to the advancement of communication and media work, thanks to its developmental leaps and diverse transformations in content, technology, and methods. Media charters serve as ethical guidelines and subjective standards that encourage media efforts toward high-quality professional performance. This performance is characterized by respect for social norms and a commitment to positive media coverage, upholding the desired principles of neutrality, credibility, and integrity. Arab media charters often focus on indicators related to general media performance without specifically addressing sports media. This makes the development of sports media charters imperative in the near future to establish a framework of professional guarantees in this important media sector. Therefore, in this modest scientific effort, which we have paved the way for with this summary, we will try to identify the extent of the sports system’s position in Arab media charters through a scientific reading of the articles of the Code of Journalistic Ethics issued by the Emirates Journalists Association, hoping to come up with at least some scientific indicators about this research hypothesis.